2010
DOI: 10.3233/jad-2010-091387
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Intake and Dementia: Systematic Review and Meta-Analysis

Abstract: Abstract.A recent meta-analysis of 4 studies published up to January 2004 suggests a negative association between coffee consumption and Alzheimer's disease, despite important heterogeneity in methods and results. Several epidemiological studies on this issue have been published since then, warranting an update of the insights on this topic. We conducted a systematic review and meta-analysis of published studies quantifying the relation between caffeine intake and cognitive decline or dementia. Data sources se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(119 citation statements)
references
References 35 publications
(139 reference statements)
6
106
2
5
Order By: Relevance
“…The observation that the protective effect of chocolate consumption on cognitive decline was observed only among subjects with low daily consumption of caffeine may suggest that caffeine is not the relevant component involved in this protective effect. It is interesting that the protective effects of caffeine on cognitive decline may be more consistent in women [23,35], but we did not observe any gender differences regarding the association of chocolate intake with a lower risk of cognitive decline. Alternatively, the potential protective effect could be due to the caffeine present in chocolate, and this effect would just be masked in the population consuming higher amounts of caffeine from other sources.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…The observation that the protective effect of chocolate consumption on cognitive decline was observed only among subjects with low daily consumption of caffeine may suggest that caffeine is not the relevant component involved in this protective effect. It is interesting that the protective effects of caffeine on cognitive decline may be more consistent in women [23,35], but we did not observe any gender differences regarding the association of chocolate intake with a lower risk of cognitive decline. Alternatively, the potential protective effect could be due to the caffeine present in chocolate, and this effect would just be masked in the population consuming higher amounts of caffeine from other sources.…”
Section: Discussionmentioning
confidence: 43%
“…The combination of caffeine and theobromine in the proportions found in cacao and chocolate has been shown to display psycho-stimulant effects [30,34]. Caffeine has been more widely explored, showing a protective effect against cognitive impairment and cognitive decline [35] and a possible preventive effect on the development of Alzheimer's disease (AD) [36]. On the other hand, the effects of theobromine have been less studied than those of caffeine, and the potential neurobiological effects of theobromine are still poorly understood [33,37], partially due to the prevalent idea that it is a weak central nervous system stimulant [38,39], and has only been showed to produce very minor subjective effects compared to caffeine [40].…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up times varied from 16 months to 30 years. Systematic review and meta-analysis of all studies investigating the association between caffeine and dementia/cognitive decline is presented by Santos et al [5] in this issue.…”
Section: Previous Longitudinal Studiesmentioning
confidence: 99%
“…Human epidemiological and animal experimentation studies as well as studies conducted in cultured cell models have shown that caffeine protects against the onset and severity of AD [19][20][21][22][23][24][25][26][27][28]. Additionally, it has been shown that it can reverse behavioral and pathological features of AD [19,21,22,24,25,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%